Effectiveness of Lime Concentration As A Modification of Turk's Reagent in Leucocyte Type Count Examination - Arham, Chaerul; Rasyid, Nur Qadri; Rianto, Rifo; Moito, Rahma (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Turk solution has a composition of glacial acetic acid, gentian violet, and distilled water. Lime (Citrus aurantifolia S) has a pH of 2.0 which is almost the same as acetic acid. Both components are weak acids that can lyse blood cells other than white blood cells. This study aims to determine the effectiveness of lime concentration as a modification of Turk's reagent in counting the number of leukocytes and knowing the concentration of 1%, 2%, or 3% which is more effective in counting the number of leukocytes. Method: This study aims to provide an overview of the effectiveness of lime concentration as a modification of turk reagent composition in counting the number of leukocytes. The research method used is the Counting Room Method. This research was conducted in August 2024 at the clinical pathology laboratory of the Muhammadiyah Makassar Polytechnic. The number of samples in this study was 4 blood samples obtained from 4 correspondents with treatment, lime concentrations namely 1%, 2%, and 3%, and turk reagent as control. Result: At 1% concentration, the average difference in leucocyte count between the control and the sample was 1,150 cells/mm3, at 2% concentration a difference of 2,788 cells/mm3 was obtained with the control, and at 3% concentration a difference of 3,638 cells/mm3 was obtained. Conclusion: It can be concluded that the concentration of lime that is effective as a modification of Turk's reagent in counting the number of leukocytes is a concentration of 1%.